Minimal residual disease and outcome characteristics in infant KMT2A-germline acute lymphoblastic leukaemia treated on the Interfant-06 protocol - Stutterheim, J; de Lorenzo, P; van der Sluis, I M; Alten, J; Ancliffe, P; Attarbaschi, A; Aversa, L; Boer, J M; Biondi, A; Brethon, B; Diaz, P; Cazzaniga, G; et al. (European journal of cancer (Oxford, England, 2022)
BACKGROUND: The outcome of infants with KMT2A-germline acute lymphoblastic leukaemia (ALL) is superior to that of infants with KMT2A-rearranged ALL but has been inferior to non-infant ALL patients. Here, we describe the outcome and prognostic factors for 167 infants with KMT2A-germline ALL enrolled in the Interfant-06 study. METHODS: Univariate analysis on prognostic factors (age, white blood cell count at diagnosis, prednisolone response and CD10 expression) was performed on KMT2A-germline infants in complete remission at the end of induction (EOI; n = 163). Bone marrow minimal residual disease (MRD) was measured in 73 patients by real-time quantitative polymerase chain reaction at various time points (EOI, n = 68; end of consolidation, n = 56; and before OCTADAD, n = 57). MRD results were classified as negative, intermediate (<5∗10-4), and high (≥5∗10-4). RESULTS: The 6-year event-free and overall survival was 73.9% (standard error [SE] = 3.6) and 87.2% (SE = 2.7). Relapses occurred early, within 36 months from diagnosis in 28 of 31 (90%) infants. Treatment-related mortality was 3.6%. Age <6 months was a favourable prognostic factor with a 6-year disease-free survival (DFS) of 91% (SE = 9.0) compared with 71.7% (SE = 4.2) in infants >6 months of age (P = 0.04). Patients with high EOI MRD ≥5 × 10-4 had a worse outcome (6-year DFS 61.4% [SE = 12.4], n = 16), compared with patients with undetectable EOI MRD (6-year DFS 87.9% [SE = 6.6], n = 28) or intermediate EOI MRD <5 × 10-4 (6-year DFS 76.4% [SE = 11.3], n = 24; P = 0.02). CONCLUSION: We conclude that young age at diagnosis and low EOI MRD seem favourable prognostic factors in infants with KMT2A-germline ALL and should be considered for risk stratification in future clinical trials.
Keywords: analýza přežití; Germ Cells; reziduální nádor; KMT2A-germline; Survival Analysis; kojenec; Prognosis; výsledek terapie; akutní lymfatická leukemie; Neoplasm, Residual; mužské pohlaví; Infant; ženské pohlaví; prognóza; Humans; zárodečné buňky; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Female; ALL; Treatment Outcome; MRD; lidé; Male